Consistency and Law Comparison in Consumer Protection Law Design in the Light of the Socially Responsible Market Economy Approach - Stefan Koos (Indonesian Journal of Economics, Social, and Humanities, 2021)
Social justice is an essential issue in the development of Indonesian law of the 21st century. Consumer protection is an aspect of social justice because it maintains "equality of arms" between suppliers and consumers. The more technological developments are integrated into social life and thus also into the business competition process, the greater the importance of consumer protection becomes, because the use of disruptive technologies, for example artificial intelligence, can shift the balance between providers and consumers in favour of economically strong providers. This will lead to the need to redefine the position of consumer protection in the Indonesian legal system. Law No. 8/1999 on Consumer Protection in its current form follows a rather ambiguous systematic approach by not clearly distinguishing between individual and social-functional protection purposes of consumer protection. The article argues for creating the methodological framework for a possible revision of the Indonesian consumer protection law with a strong integration of cultural-empirical and scientific-systematic viewpoints.